Novel Z-scheme In2S3/Bi2WO6 core-shell heterojunctions with synergistic enhanced photocatalytic degradation of tetracycline hydrochloride. (10th March 2022) - He, Zuming; Siddique, Muhammad Saboor; Yang, Hanpei; Xia, Yongmei; Su, Jiangbin; Tang, Bin; Wang, Lina; Kang, Li; Huang, Zhengyi
Abstract: Semiconductor photocatalytic technology is an effective strategy to cope with the current environmental issues. Therefore, the development of low-cost and environment-friendly catalysts with high efficacy has become a research focus and emphasis. Herein, novel Z-scheme In2 S3 /Bi2 WO6 core-shell structure composites were controllably prepared by template and hydrothermal route. Highly improved photocatalytic degradation of tetracycline hydrochloride (TCH) over In2 S3 /Bi2 WO6 core-shell composites was observed under visible-light (VL) irradiation (∼96.0%), which was 2.4 and 2.1 folds higher than that of In2 S3 and Bi2 WO6, respectively. The excellent oxygen activation and catalytic performance was ascribed to the synergistic effects of built-in electric field to ensure easy charge exchange at the interface of In2 S3 and Bi2 WO6, Z-scheme charge transfer path and the extended range of VL absorption. Superoxide radical (·O- 2) and hydroxyl (·OH) radicals were verified to be involved in the photocatalytic reaction by the active species capture experiment and the electron spin response (ESR) detection. The recycling experiments demonstrate the excellent stability and reusability of the In2 S3 /Bi2 WO6 . In addition, in accordance with the experimental results, the highly efficient Z-scheme photocatalytic mechanism and degradation paths were proposed. This work provided a new way for preparation of Z-scheme core-shell composites which had broad applications prospect in environmental remediation. Graphical abstract: The possible photocatalytic mechanism for TCH degradation in the Z-scheme In2 S3 /Bi2 WO6 system. Image 1 Highlights: Novel In2 S3 /Bi2 WO6 core-shell heterojunctions were acquired. The In2 S3 /Bi2 WO6 heterojunctions exhibits superior photocatalytic activity. Boosting photocatalytic performance is due to the synergistic effects. · O- 2 and · OH radicals played a decisive role in the photocatalytic reaction.